Clinical Management and Surgical Outcomes of Wandering Spleen with Splenic Torsion in Pediatric Patients: A Case Report - Shaban Memeti; Saimir Kuci; Toni Ristevski; Lazar Todorovic; Marijan Kamilovski; Blagica Krsteska; Haris Sulejmani (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Wandering Spleen is a rare condition in which the splenic ligaments are abnormally loose or absent. This makes the Spleen more mobile and increases the risk of torsion.